RNA-binding protein IGF2BP2 enhances circ_0000745 abundancy and promotes aggressiveness and stemness of ovarian cancer cells via the microRNA-3187-3p/ERBB4/PI3K/AKT axis - Shengtan Wang; Zaihong Li; Genhai Zhu; Lan Hong; Chunyan Hu; Kang Wang; Kaiying Cui; Chunbo Hao (BMC, 2021)
Abstract Background Circular RNAs (circRNAs) are increasingly recognized as important regulators in cancer including ovarian cancer (OC). This work focuses on the effects of circ_0000745 on the OC development of and molecules involved. Methods Expression of circ_0000745 in collected OC tissues and the acquired OC cell lines was examined by RT-qPCR. The stability of circ_0000745 in cells was examined by RNase R treatment. The target transcripts interacted with circ_0000745 were predicted using bioinformatic systems. Gain- and loss-of-function studies of circ_0000745, microRNA (miR)-3187-3p and erb-b2 receptor tyrosine kinase 4 (ERBB4) were conducted to determine their functions on proliferation, migration, invasion and stem cell property of OC cells. Results Circ_0000745 and ERBB4 were abundantly expressed while miR-3187-3p was poorly expressed in OC tissues and cells. Circ_0000745 sequestered miR-3187-3p and blocked its repressive effect on ERBB4. Downregulation of circ_0000745 reduced proliferation, aggressiveness, epithelial-mesenchymal transition, and stemness of SK-OV-3 cells, but this reduction was blocked upon miR-3187-3p inhibition or ERBB4 upregulation. By contrast, artificial induction of circ_0000745 upregulation, miR-3187-3p upregulation and ERBB4 downregulation led to inverse trends in ES-2 cells. ERBB4 promoted the phosphorylation of the PI3K/AKT signaling pathway. An RNA binding protein IGF2BP2 was found to circ_0000745 bind to and promote its expression and stability. Conclusion This study demonstrated that circ_0000745 upregulated by IGF2BP2 promotes aggressiveness and stemness of OC cells through a miR-3187-3p/ERBB4/PI3K/AKT axis. Circ_0000745 may serve as a promising target for OC treatment.